2022
DOI: 10.1111/fme.12600
|View full text |Cite
|
Sign up to set email alerts
|

An integrated scheme for the management of drifting fish aggregating devices in tuna purse seine fisheries

Abstract: Drifting fish aggregating devices (dFADs) are extensively used in modern tuna purse seine fisheries. The use of dFADs has greatly improved fishing efficiency and generated substantial economic returns in purse seine fisheries, but adverse impacts on tuna juveniles, associated species and marine ecosystems are still of concern.Based on an analysis of current challenges in dFAD management measures in tuna regional fishery management organisations (t-RFMOs), we explored opportunities to strengthen dFAD management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Some unintended effects occurred with an increasing number of silky sharks caught accidentally by PS vessels, particularly in the northern area of the IO where tuna vessels were not used to fish with fewer active FADs at sea (Tolotti et al., 2022). Because of important social costs related to bycatch, stranding, ocean pollution, etc., FADs are under scrutiny by RFMOs, and many experts around the world advocate for a more stringent limitation of their use (Fonteneau et al., 2015, Lennert‐Cody et al., 2018, Hanich et al., 2019, Gomez et al., 2020, Song & Shen, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some unintended effects occurred with an increasing number of silky sharks caught accidentally by PS vessels, particularly in the northern area of the IO where tuna vessels were not used to fish with fewer active FADs at sea (Tolotti et al., 2022). Because of important social costs related to bycatch, stranding, ocean pollution, etc., FADs are under scrutiny by RFMOs, and many experts around the world advocate for a more stringent limitation of their use (Fonteneau et al., 2015, Lennert‐Cody et al., 2018, Hanich et al., 2019, Gomez et al., 2020, Song & Shen, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of FAD management measures taken by RFMOs can be found in Davies et al. (2014), Song and Shen (2022) or Baidai et al. (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations